Ulcerative dermatitis due to feline infectious peritonitis virus infection in a cat - Avila, Vicente A.; Rissi, Daniel R. (Brazilian Journal of Veterinary Pathology, 2020)
Feline infectious peritonitis (FIP) is one of the most prevalent viral diseases of wild and domestic cats. Despite of its multisystemic character, cutaneous lesions of FIP have been rarely described. A skin biopsy from a 14-month-old male neutered domestic shorthaired cat with a slightly raised, 5 mm in diameter ulcer on the dorsal cervical area and a presumptive clinical diagnosis of FIP was submitted for histological examination. Histological changes consisted of ulcerative dermatitis with perivascular, periadnexal, and interstitial accumulations of neutrophils, macrophages, lymphocytes, and plasma cells with areas of vasculitis. Immunohistochemistry for feline coronavirus revealed intralesional clusters of antigen within macrophages. FIP should be considered in cases of papular to nodular or ulcerative skin lesions in cats when occurring in conjunction with clinical signs of systemic disease consistent with FIP.